A Newly Designed Enterocutaneous Esophageal Fistula Model in the Pig. (June 2016) - Rahmi, Gabriel; Perretta, Silvana; Pidial, Laetitia; Vanbiervliet, Geoffroy; Halvax, Peter; Legner, Andras; Lindner, Veronique; Barthet, Marc; Dallemagne, Bernard; Cellier, Christophe; Clément, Olivier
Background . Fistulas after esophagectomy are a significant cause of morbidity and mortality. Several endoscopic treatments have been attempted, with varying success. An experimental model that could validate new approaches such as cellular therapies is highly desirable. The aim of this study was to create a chronic esophageal enterocutaneous fistula model in order to study future experimental treatment options. Methods . Eight pigs (six 35-kg young German and two 50-kg adult Yucatan pigs) were used. Through a left and right cervicotomy, under endoscopic view, 1 (group A, n = 6) or 2 (group B, n = 7) plastic catheters were introduced into the esophagus 30 cm from the dental arches bilaterally and left in place for 1 month. Radiologic and endoscopic fistula tract evaluations were performed at postoperative day (POD; 30) and at sacrifice (POD 45). Results . Three fistulas were excluded from the study because of early (POD 5) dislodgment of the catheter, with complete fistula closure. At catheter removal (POD 30), the external orifice was larger in group B (5.2 ± 1.1 mm vs 2.6 ± 0.4 mm) with more severe inflammation (72% vs 33%). At POD 45, the external orifice was closed in all fistulas in group A and in 1/7 in group B. At necropsy, the fistula tract was still present in all animals. Yucatan pigs showed more complex tracts, with a high level of necrosis and substantial fibrotic infiltration. Conclusions . In this article, we show a reproducible, safe, and effective technique to create an esophagocutaneous fistula model in a large experimental animal.